PERANCANGAN APLIKASI CHORD UKULELE BERBASIS ANDROID MENGGUNAKAN ALGORITMA TURBO BOYER MOORE - Purba, Sry Asliza Br (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2017)
Ukulele includes a portable instrument that is easy to carry anywhere because of its small size. In playing ukulele certainly not apart from the chord. Chord better known as "key, chord is harmonization and combination of tones produced when played simultaneously, chord is used to accompany a song. For people who are new to learning and starting to learn ukulele autodidactically, first need to know the chord of the song to be sung, usually to know the chords of a song, people will look for references on the internet and music magazines or ask the more understanding. However, due to lack of information about chord ukulele make people have difficulty and need media information to know chord of a song to be sung. The application will be designed is an android-based application and offline, this can minimize the cost of internet quota and the purchase cost of ukulele chord books. The Turbo Boyer-Moore algorithm is a variation of the Boyer-Moore algorithm. Turbo Boyer Moore has two advantages, allowing to skip over the factor of the text and Turbo Boyer Moores technique allows Turbo shifts.